AL-‘ALAQAH BAYNA ITTIJAHAT TALABAT JAMI‘AT MARA LIL-TIKNOLOGIA (UITM) NAHWA TA‘ALLUM AL-NAHW AL-‘ARABI WA MUSTAWA FAHMIHIM LIL-AF‘AL AL-MUTA‘ADDIYAH WA AL-LAZIMAH - Mohamad Rofian Ismail; Azman Che Mat; Aiman Hakin Azemaizan (El-Tsaqafah : Jurnal Jurusan PBA, 2026)
This study aims to examine the relationship between students’ attitudes toward learning Arabic grammar and their level of understanding of transitive and intransitive verbs, a linguistic area that has received limited attention in experimental research. The study employed a quantitative, descriptive correlational approach and included the entire research population, consisting of 83 male and female final-year students enrolled in an Arabic language course at Universiti Teknologi MARA. A census sampling technique was used due to the small and easily accessible population. The study utilized a structured questionnaire comprising four sections: demographic data, level of verb usage, level of grammatical understanding, and students’ attitudes toward learning grammar. The overall Cronbach’s alpha coefficient (0.89) indicated a high level of reliability. Descriptive statistical analysis revealed that students’ attitudes toward grammar were high (M = 4.22, SD = 0.67), as was their level of grammatical understanding (M = 3.81, SD = 0.81). Pearson correlation analysis showed a moderate to strong positive relationship between students’ attitudes and their level of grammatical understanding (r = 0.66, p < 0.001). This study contributes by providing quantitative empirical evidence linking psychological attitudes with grammatical achievement in the context of Arabic language learning—an area that still lacks sufficient field-based research, particularly in the Malaysian educational setting. The findings recommend the adoption of interactive, technology-supported instructional strategies to foster positive attitudes toward Arabic grammar. The study also calls for future research to explore additional variables, such as language anxiety, learning strategies, and the impact of technology on the development of learners’ grammatical competence.